Impact of Indonesian Healthcare Worker in Stunting Eradication - Ray Wagiu Basrowi; Charisma Dilantika; Nova Lidia Sitorus; Mikhael Yosia (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Even though the number of cases has reduced yearly, stunting is still a significant condition affecting Indonesian children. The fight against stunting includes attention to sensitive and specific interventions addressing the direct and indirect causes of stunting. Healthcare workers, as front liners, play a significant role in the intervention and eradication of stunting and are actively involved in the prevention, education, advocation, and data gathering surrounding stunting. Though vital, the role of healthcare workers in the fight against stunting and its impacts have never been discussed extensively, partly due to the vast variation of healthcare workers and layers of medical services (from primary care to advance hospitalization) included in the care for stunting. This review aims to look at available literature resources that fully describe the numerous roles and the impact healthcare workers had on eradicating stunting in Indonesia. While the healthcare roles in providing intervention of stunting (e.g., medical doctors in the prescription of ONS) is essential, it is crucial to equip healthcare (and the community) with sufficient knowledge of stunting.